Early Summer Drought Stress During the First Growing Year Stimulates Extra Shoot Growth in Oak Seedlings (Quercus petraea) - Turcsán, Arion; Steppe, Kathy; Sárközi, Edit; Erdélyi, Éva; Missoorten, Marc; Mees, Ghislain; Mijnsbrugge, Kristine V. (Frontiers in Plant Science, 2016)
More severe summer droughts are predicted for mid-latitudes in Europe. To evaluate the impact on forest ecosystems and more specifically on forest regeneration, we studied the response to summer drought in oak seedlings (Quercus petraea). Acorns were collected from different mother trees in three stands in Belgium, sown in pots and grown in non-heated greenhouse conditions. We imposed severe drought on the seedlings in early summer by first watering the pots to saturation and then stopping any watering. Weight of the pots and stomatal conductance were regularly measured. Re-watering followed this drought period of five weeks. Height of the seedlings and apical bud development were observed. Stomatal resistance increased towards the end of the experiment in the drought-treated group and was restored after re-watering. The seedlings from the drought treatment displayed a higher probability to produce additional shoot growth after re-watering (p ≤ 0.05). A higher competition for resources (two plants per pot) increased this chance. Although this chance was also higher for smaller seedlings, the actual length of the extra growth after re-watering was higher for larger seedlings (p ≤ 0.01). Both in the drought-treated and in the control group the autochthonous provenance growing on a xeric site produced less extra shoots compared to the two other provenances. Finally, stressed plants showed less developed apical buds compared to the control group after re-watering, suggesting a phenological effect on the growth cycle of oaks (p ≤ 0.0001). The higher chance for an extra shoot growth after the drought period can be considered as a compensation for the induced growth arrest during the drought period.